Pengaruh Pengetahuan, Kemudahan, dan Sistem Pembayaran terhadap Minat Investasi Emas Digital pada Generasi Milenial (Studi pada Mahasiswa Fakultas Bisnis dan Ilmu Sosial Universitas Dian Nusantara Jakarta) - Pribowo, Karman; Fathihani, Fathihani (Jurnal Manajemen dan Pemasaran Digital, 2023)
This study aims to look at the factors that influence the intention to invest in gold digitally. This study uses a quantitative approach with multiple linear analysis methods. The population in this study were students of the Faculty of Business and Social Sciences, Dian Nusantara University, Jakarta. The sampling technique in this study used purposive sampling. The data is primary data using a questionnaire with a sample of 105 respondents. The independent variables in this study are knowledge, convenience, and payment systems while the dependent variable in this study is interest in investing in digital gold. The results of this study indicate that partially knowledge, convenience, and payment systems affect interest in investing in digital gold. Simultaneously knowledge, convenience, and payment systems affect interest in digital gold investment.